Caracterização morfológica do espaço arquitetônico de habitações concebidas para condomínios horizontais - Ludovico, Sonia Santos de Alencar (2014)
This work applies the morphological analysis of a sample, composed by a selection of architectural projects of housing were created for horizontal condons in Cuiaba-MT. Assuming that, among some factors which impress quality conditions to a house, there are: flexibility and enlarging (development capacity), regardless the building system used, the condition for this to occur totally depends on the form generated in the project. Considering that the geometric configuration of the projected spaces enables conducing or not to a form which potentiates the evolutionary capacity, dynamism and longevity of the housing, this work intents, through the application of the shape grammar methodology, to perform the analysis of the architectural plans from the projects sample. With this, it’s possible: identify the vocabulary of emerging forms of conceptional process; to identify the kind of flexibility proposed on the projects as one criterion of project quality; and detected the evolutionary potential of housing, establishing a parallel between the prefabricated and conventional housing. As a result of analyzes it was observed that in both cases, both conventional housing as prefabricated, meet the design criteria of quality, which determines the suitability or not quality of designs conditions, it is not related to constructive model adopted, the design quality is determined by skill and designer's vision to predict conditions that enable and foster the application of quality principles however, aspects such as the housing capacity expansion observed through its evolutionary potential; enlarging possibilities and continuous flexibility of housing were identified and measured in all the projects analyzed in this research.